Do vaccinations reduce inequality in Covid-19 mortality? Evidence from England. (July 2022) - Sá, Filipa
Abstract: The Covid-19 pandemic has affected countries and regions to varying degrees. In this paper, I examine the socioeconomic determinants of Covid-19 mortality and study whether vaccinations have affected the relationship between those determinants and Covid-19 mortality rates across local areas in England. I use monthly data for 6791 Middle Layer Super Output Areas for the period from March 2020 to April 2021 and estimate a spatial correlations model with local authority and time fixed effects. To study whether vaccinations have affected the relationship between socioeconomic determinants and Covid-19 mortality, I extend the model to include interactions between socioeconomic variables and the lagged cumulative vaccination rate. I find that Covid-19 mortality is higher in areas that have an older population, a larger share of Asian population, higher population density, lower income, poorer pre-existing health and a larger share of employment in health and social care occupations. Vaccinations have weakened the links between mortality and these socioeconomic characteristics. These findings highlight the importance of making vaccines widely available and encouraging take-up, to reduce inequality in Covid-19 mortality across socioeconomic groups. Highlights: Covid-19 mortality is higher in areas of England with an older population. Mortality is higher in areas with a larger share of Asian population. Mortality is higher in areas with higher population density and lower income. Mortality is higher in areas with poorer health and more health workers. Vaccines weaken the links between mortality and socioeconomic characteristics.